Cardiac tamponade: a rare but preventable complication of central venous catheter in neonates - Atmawidjaja, Raymond Warouw; Zainal Abidin, Mohd Azri; Ismail, Intan Hakimah (Malaysian Medical Association, 2016)
Pericardial effusion with cardiac tamponade is a rare and life-threatening complication of peripherally inserted central catheter (PICC) in a neonate. We report a 33-week preterm neonate who had sudden clinical deterioration at day seven of total parenteral nutrition regime via PICC. Recognition of pericardial effusion with cardiac tamponade in neonates with a PICC requires a high index of suspicion and steps in prevention include proper catheter tip placement and continuous monitoring of line position and function.